Validation of the DLQI questionnaire in assessing the disease burden and principal aspects related to life quality of vitiligo patients - Fekete, Laszlo; Iantovics, Laszlo Barna; Fekete, Gyula Laszlo (Frontiers in Psychology, 2024)
According to many studies, vitiligo has a negative psychological influence on the patient's life. Multiple factors contribute to the severity of the vitiligo disease burden, among which the most important are self-esteem, stress, and stigma. We aimed to measure the importance of health-related life quality in assessing disease burden in patients with vitiligo. We formulated an HA, which is the principal hypothesis, claiming a single fundamental factor that characterizes the life quality of patients with vitiligo. We also formulated 10 important research questions related to the quality of life that can be generally formulated for patients with dermatological illnesses but particularly suited for vitiligo patients. These research questions capture fundamental aspects of the health-related quality of life of vitiligo patients influenced by symptoms and feelings, daily activities, leisure, job and education, personal relationships, and treatment. These also cover specific aspects related to the quality of life, such as skin-caused sexual difficulties, difficulties in social relationships, and difficulties in performing sports, among others. The Dermatology Life Quality Index (DLQI) questionnaire measures the health-related quality of life of persons suffering from skin diseases. We applied this generic questionnaire to patients with vitiligo. Following a set of inclusion and exclusion criteria, we obtained 114 carefully selected patients who responded to all the questions. This study also validated the DLQI questionnaire on persons who suffer from vitiligo. We investigated whether DLQI has acceptable internal consistency by applying Cronbach's alpha internal consistency indicator (Cα). The obtained Cα = 0.914 indicates excellent internal consistency. We also examined whether all the questions in the questionnaire were mathematically consistent, which we finally proved. It was not necessary to remove any of the questionnaire questions. To prove our HA, a Principal Axis Factoring (PAF) was applied, verifying the assumptions regarding the Average Variance Extracted (AVE) and Convergent Validity (CV). HA proved that applying PAF on DLQI resulted in extracting a single general vitiligo latent factor of life quality, with an initial eigenvalue = 5.671, SS loadings = 5.2, and 52 % of the total cumulative variance explained. Diverse statistical analyses were applied to analyze the 10 formulated research questions. The results of the analysis of the research questions are presented and discussed in the manuscript. One of the conclusions related to the analysis of a research question was that sex had the lowest correlation with the latent life quality factor identified for vitiligo patients.